Draining and filling of ice-dammed lakes at the terminus of surge-type Dań Zhùr (Donjek) Glacier, Yukon, Canada - Kochtitzky, Will; Copland, Luke; Painter, Moya; Dow, Christine (NRC Research Press (a division of Canadian Science Publishing), 2020)
Recent surges of Dań Zhùr (Donjek) Glacier have formed lakes at the glacier terminus that have drained catastrophically, resulting in hazards to people and infrastructure downstream. Here we use air photos and satellite imagery to describe lake formation, and the timing of filling and draining, since the 1930s. Between the 1930s and late 1980s, lakes were typically small (<0.6 km2), took many years to form after a surge event, and drained slowly as they were displaced by the glacier advancing in the next surge. However, since 1993, the lakes have become larger (>1 km2) and drain rapidly through or under the glacier by breaking a terminal ice dam. For the past two surges, since 2001, the lakes formed during or immediately after a surge in an increasingly larger basin between the Neoglacial maximum moraine and an increasingly smaller maximum terminus extent. Most recently, the 2012–2014 surge created a lake that drained in summer 2017, refilled, and drained again in both summer 2018 and summer 2019. The 2019 lake was 2.2 km2, the largest on record, and drained entirely within 2 days. While a lake is unlikely to form again before the next expected surge in the mid-2020s, future surges of Dań Zhùr Glacier are still likely to create terminal lakes, necessitating continued monitoring for surge activity and lake formation. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.